Studies on the activation of complement by dengue 2 antigen. - Sioson, Jocelyn S. (1983)
The ability of crude dengue 2 virus antigen to activate the alternate complement pathway, under in vitro conditions, was investigated. Crude dengue 2 antigen consisted of dengue 2 infected mouse brain suspension, partially purified by ultracentrifugation at 10,000 rpm for 1 hour. 3 experimental designs were employed to determine alternate complement activation. The initial method consisted of parallel assays in VBS-Mg++ -EGTA and VBS-Mg++, wherein residual CH50 units of Guinea Pig Complement (GPC) was quantitated following incubation of 50 CH50 units of GPC and 50 LD50 units of crude dengue 2 antigen at 37(degree centigrade) for 1 hour. The results of the unitage titration for residual complement activity indicated that there was no activation of complement, via the alternate pathway, by the crude dengue 2 antigen. The failure to activate complement by 50 LD50 units of crude dengue 2 was suspected to be due to insufficient quantity of antigen trigger. Consequently, block titrations testing 4 other antigen concentrations, i.e., 500, 5000, 50000 and 500000 LD50 units of crude dengue 2 antigen against 5 concentrations of GPC, containing 10, 5, 2, 1 and 0.5 CH50 units, and Human Complement (HC), containing 5, 2, 1 and 0.5 CH50 units were performed. The 1st block titration method was essentially the same as the 2nd block titration except for the use of unsensitized Sheep Red Cells (SRBC) in the former and sensitized SRBC in the latter. Also, in the 2nd block titration method, a pre-incubation period of 30 minutes at 37(degree centigrade) was included to allow crude dengue 2 antigen and HC/GPC to react prior to the addition of the sensitized SRBC. The results from both block titrations suggested that there was no alternate complement activation. It appears that these observations could be related to an earlier finding by Platts-Mills and Ishizaka (44) that EGTA is inhibitory to hemolysis of SRBC, whether sensitized or unsensitized. The observations in this study cannot fully explain why crude dengue 2 virus antigen failed to activate complement via the alternate pathway. The possibility exists, though, that the nature of the dengue 2 antigen used in the study may not be the same as that which is or are circulating during human dengue infections wherein alternate activation of complement was demonstrated. This preliminary investigation would lead to further critical study on the role of dengue viruses in alternate complement activation and thus, contribute to a better understanding of the pathogenesis and pathophysiology of DHF/DSS.